Epidemiología de la patología otorrinolaringológica ambulatoria y quirúrgica en población mayor de 65 años en el Hospital Clínico de la Universidad de Chile - Aróstica V., Luis; Aravena C., Oscar; Aguirre R., Noemí; Walker J., Katherine (Revista Hospital Clínico Universidad de Chile, 2011)
Introduction: The otolaryngology (ear, nose and throat (ENT)) pathology is a common ambulatory cause of consultation in an elderly country as Chile. Aims: Characterize the ENT diagnosis in ambulatory elderly population more than 65 years old consultant on ENT clinic of HCUCH (Hosptial Clínoco Universidad de Chile) during 2009. Patients and Methods: descriptive transversal retrospective study. ENT diagnosis was rescued of clinical archives. Anatomicalfunctional groups, specific diagnosis and sex were tabulated. A patient could have more than one diagnosis. STATA statistical analysis was performed. Results: 148 elderly (204 diagnosis) consulted during 2009, average age 74,08±6,87 years old, 65,54% women. The most frecuent groups were the vestibular-auditive (n=133; 65,20%), naso-sinusal (n=36; 17,64%) and pharingo-laryngeal (n=17; 8,33%). The most frecuent specific diagnosis were prebycusis (n=43; 21,08%), earwax (n=28; 13,73%), allergic rhinitis (n=17; 8,33%) and unspecified vertigo (n=13; 6,37%). There were not significant differences between gender in any specific diagnosis. Discussion: The diagnostic profile is consistent to age group. Results agree with the high frequency of presbycusis, but differ in the high presence of earwax and allergic rhinitis above other expected diagnostics. Conclusion: new chilean epidemiologic information of ambulatory and surgical ENT pathology was provided.